Phase-field modelling of as-cast microstructure evolution in nickel-based superalloys - Warnken, N; Ma, D; Drevermann, A; Reed, R; Fries, S; Steinbach, I (2009)
A modelling approach is presented for the prediction of microstructure evolution during directional solidification of nickel-based superalloys. A phase-field model is coupled to CALPHAD thermodynamic and kinetic (diffusion) databases, so that a multicomponent alloy representative of those used in industrial practice can be handled. Dendritic growth and the formation of interdendritic phases in an isothermal (2-D) cross-section are simulated for a range of solidification parameters. The sensitivity of the model to changes in the solidification input parameters is investigated. It is demonstrated that the predicted patterns of microsegregation obtained from the simulations compare well to the experimental ones; moreover, an experimentally observed change in the solidification sequence is correctly predicted. The extension of the model to 3-D simulations is demonstrated. Simulations of the homogenization of the as-cast structure during heat treatment are presented. © 2009 Acta Materialia Inc.